Adipose-derived mesenchymal stem cells enhance regeneration in a chronic peripheral sciatic nerve injury Sprague-Dawley rat model - Widodo, Wahyu; Dilogo, Ismail Hadisoebroto; Kamal, Achmad Fauzi; Antarianto, Radiana Dhewayani; Wuyung, Puspita Eka; Siregar, Nurjati Chairani; Octaviana, Fitri; Kekalih, Aria; Suroto, Heri; Aprilya, Dina; Canintika, Anissa Feby (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Obtaining optimal functional outcomes in patients with chronic peripheral nerve injuries (PNIs) remains challenging due to the limited regeneration of the neuromuscular junction (NMJ). Adipose-derived mesenchymal stem cells (AD-MSCs) can differentiate into Schwann-like cells, secrete neurotrophic factors, and recruit native Schwann cells. This study aimed to analyze the effects of AD-MSCs on functional outcomes in a chronic PNI model. METHODS An in vivo study was performed using 20 male Sprague-Dawley rats with chronic PNI of the right sciatic nerve. Rats were divided into two groups: the AD-MSC group (n = 10), receiving human AD-MSC injections in the NMJ; and the control group (n = 10), receiving normal saline injections. Walking track analysis and electrophysiological assessments were performed 8 weeks after the nerve repair. Postmortem gastrocnemius muscle weights and immunohistochemical examinations were also performed. RESULTS The AD-MSCs showed significantly larger fiber diameters than the control group (45.54 [13.1] versus 35.46 [6.64]; p = 0.011). While clinical, electrophysiological, and gastrocnemius muscle weight data suggested a trend toward improved outcomes in the AD-MSCs group, the differences were not statistically significant. CONCLUSIONS AD-MSC implantation may enhance nerve regeneration, as demonstrated by a better outcome profile in the AD-MSCs group.